THE ROLE OF OUT-OF-SCHOOL ENGLISH LITERACY ACTIVITIES IN PROMOTING STUDENTSâ ENGLISH LITERACY - Lilies Setiasih (TEFLIN Journal: A publication on the teaching and learning of English, 2014)
Â This paper reports on a case study of the role of out-of-school English literacy activities in promoting studentsâ English literacy at an elementary school in Bandung. The study is an attempt to respond to controversy among decision makers about the idea of offering English at elementary schools and the reality that at the school where the research was conducted, English is fully used as a means of instruction for English, Mathematics, and Science. Considering that literacy is shaped in socio-cultural contexts, the researcher assumed that the students acquired and developed their English literacy not only at school but also outside of school. Their out-of-school English literacy activities might contribute to their English literacy development. The research aims were to investigate the studentsâ English literacy level and to identify their out-of-school literacy activities. The theoretical framework covered the cognitive and socio-cultural theories of literacy. The research results were: 1) the majority of the fourth grade students were in early advanced and advanced levels for the aspects of reading and writing proficiency; and 2) their out-of-school English literacy activities played an important role in building their English literacy.Â